Mango Quality Measurement System Based on Ripeness, Size, and Spot Area Using Fuzzy Inference System - Aziz Rabih Rabbani; Muhammad Faiz Assariy; Daffa Zulqisthi; Chika Hayya Sabillah; Shalinadira Koswara; Lola Amelia; Iofema Malika; Hilda Fitria Hidayah; Fildza Khairunida; Annisa Pertiwi Hakim; Atikah Fahni; Mrr Lukie Trianawati (Batrisya Education, 2025)
Mango (Mangifera indica) quality assessment poses challenges in traditional grading methods, primarily relying on visual inspection, which can be subjective. This research aims to develop a Fuzzy Inference System (FIS) for evaluating mango quality based on parameters such as color, size, and spots. A qualitative data collection approach was employed through literature review and expert opinions, followed by the application of fuzzy logic using MATLAB to analyze the parameters affecting quality. The results demonstrate that mangoes classified as